The Values of Islamic Education in Enmaen Tradition Toward Madurese in Suka Maju Village, Sungai Ambawang District - Umam, Saiful; Wahjoeharjanto, Djoko; Pratama, Ari Alfian (KARSA: Journal of Social and Islamic Culture, 2019)
Enmaen This tradition is carried out after marriage most of couples that carry out this Enmaen tradition do not understand that actually there are many values in that tradition has the same line with Al-qur’an and hadist. The purpose of this research is to find the values in the tradition which has been done for long time by maduranese in the west of Kalimantan. This research used qualitative method with etnografic and descriptive analysis. The western culture which comes to Indonesian rapidly makes some of Madurenese traditions in Suka Maju disappear including the Enmaen tradition itself. It happens because the society, especially Maduranese in coundutcing the tradition like Enmaen, just follow the habit from ancestor, whitout understand about the meaning of this tradition. The Islamic education values in Enmaen tradition are religious values, social empatic, responsibility, loving the country and tolerance.